Disease caused by the Ebola virus: from theory to practice - K. V. Zhdanov; I. V. Holikov (Журнал инфектологии, 2015)
In the present paper summarizes the results of recent epidemiological, clinical, virological research aimed at studying the infection caused by the Ebola virus. Particular attention is paid to organizational measures to prevent the disease. Described principles of medical care to patients with Ebola hemorrhagic fever. Detailed part of the Medical Service of the Russian Federation Ministry of Defense in the establishment and organization of the martial infectious hospital with 100 beds in the Republic of Guinea.